Dynamic Analysis of Environmental Degradation and Economic Activities in the Asia-Pacific Region - Lestari, Yova Tri; Kurniawan, Mahrus Lutfi Adi; Khan, Zafar (Journal of Management Studies and Development, 2024)
Economic growth is crucial for assessing a country's economic success, measured by its per capita income increase over time, primarily through Gross Domestic Product (GDP). This study investigates the impact of Gross Fixed Capital Formation (GFCF), energy consumption, CO2 emissions, and renewable energy on economic growth in the Asia-Pacific region from 2016 to 2021. Using the Difference Generalized Method of Moments (Difference GMM) and Stata 14, the findings show that GFCF positively influences economic growth in developing countries but not significantly in developed ones. Energy consumption positively affects economic growth in developing countries, but not in developed ones. CO2 emissions have no significant impact on economic growth. Renewable energy negatively affects economic growth in developing countries, while its impact is insignificant in developed ones.